2022
DOI: 10.21037/tcr-22-54
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of sintilimab combination therapy for the treatment of 48 patients with advanced malignant tumors

Abstract: Background: Sintilimab is a recombinant fully human anti-programmed death 1 (PD-1) monoclonal antibody that blocks the interaction of PD-1 with its ligand. We evaluated the safety and efficacy of sintilimab combined with chemotherapy and targeted therapy in the treatment of advanced malignant tumors. Methods:We performed a retrospective analysis of the clinical data of patients with advanced malignant tumors treated with sintilimab combined with chemotherapy and targeted therapy admitted to the Third

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…As a PD-1 inhibitor, sintilimab is currently approved in China but not in other countries for tumor immunotherapy. Sintilimab displays few adverse reactions and significant efficacy against a variety of solid tumors [7]. However, there are limited reports about the treatment of UC with PD-1 inhibitor therapy alone or combined with other chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…As a PD-1 inhibitor, sintilimab is currently approved in China but not in other countries for tumor immunotherapy. Sintilimab displays few adverse reactions and significant efficacy against a variety of solid tumors [7]. However, there are limited reports about the treatment of UC with PD-1 inhibitor therapy alone or combined with other chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The time of occurrence was only 13 days after the treatment onset, which may be the first case report in clinical of sintilimab related ICIAM in China. Huang et al reported in a study that 48 patients with various advanced tumors were treated with sintilimab, and one of them developed ICIAM (G1) (13). Huan Bi et al reported a case with lung squamous cell carcinoma (SCC) that developed ICIAM within 6 days plus three cycles after receiving sintilimab treatment (21 days/cycle) (14).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the severe and fatal hepatotoxicity resulting from pazopanib therapy observed in RCC, monitoring hepatic function is urgently required during administration [ 167 ]. Further, combination therapy with sintilimab and chemotherapy (gemcitabine, oxaliplatin, capecitabine, irinotecan, nab-paclitaxel, tegafur, or nedaplatin) or sintilimab plus other anti-angiogenic agents (anlotinib or sorafenib) showed acceptable safety with rises in the treatment efficacy and DCR for advanced tumors like RCC [ 168 ]. It should be noted that due to the few adverse reactions and proven efficacy, sintilimab combination therapy can be applied as a potent strategy for the treatment of advanced RCC.…”
Section: Anti-pd-1 Antibody In Rcc Patientsmentioning
confidence: 99%